A combined discussion: Coaches roundtable discussion regarding combined event planning - Dellemann, M. (Techniques Magazine, 2025)
I´ve spent most of my 16 years as a coach trying to figure out the optimal way to train my combined-event athletes (pentathlon, heptathlon, and decathlon) and athletes who compete in multiple events. Thanks to the USTFCCCA Convenstion and the Track & Field Academy I´ve gained a surplus of helpful knowledge; however, one topic that was rarely covered: how coaches choose to balance the multi-athlete of combined event athlete thorugh training and competition. At Northern Michigan University, we have six to seven competitions scheduled both indoor and outdoor, including out GLIAC Conference Championships, so our athletes have 12 to 14 opportunities to compete in their given events. It is unreasonable to expect them to compete in all their events at every meet. On top of that, outside of the NCAA Championships, only one to three meets per season actually give the athletes the opportunity to compete in a combined event (pentathlon/heptathlon in indoor, heptathlon/decathlon in outdoor).